Development of acetazolamide-loaded, pH-triggered polymeric nanoparticulate in situ gel for sustained ocular delivery: in vitro. ex vivo evaluation and pharmacodynamic study. (September 2014) - Singh, Jyotsana; Chhabra, Gulshan; Pathak, Kamla
Abstract The objective of research was to develop a novel pH-triggered polymeric nanoparticulate in situ gel (NP-ISG) for ophthalmic delivery of acetazolamide (ACZ) to enhance the conjunctival permeation and precorneal residence time of the formulation by overcoming the limitations of protective ocular barriers. Nanoparticles (NP1--NP12) were developed by nanoprecipitation method and evaluated for pharmacotechnical characteristics including transmission electron microscopy. The optimized formulation, NP10 was dispersed in carbopol 934 P to form nanoparticulate in situ gels (NP-ISG1--NP-ISG5). NP-ISG5 was selected as optimized formulation on the basis of gelation ability and residence time. Ex vivo transcorneal permeation study exhibited significantly higher ACZ permeation from NP-ISG5 (74.50 ± 2.20 mg/cm2) and NP10 (93.5 ± 2.25 mg/cm2) than eye drops (20.08 ± 3.12 mg/cm2) and ACZ suspension (16.03 ± 2.14). Modified Draize test with zero score indicated nonirritant property of NP-ISG5. Corneal toxicity study revealed no visual signs of tissue damage. Further, NP-ISG5 when tested for hypotensive effect on intraocular pressure (IOP) in rabbits revealed that NP-ISG5 caused significant decrease in IOP (p < 0.05) in comparison to eye drops. Conclusively, NP-ISG5 may offer intensive management of glaucoma via higher permeation, prolonged precorneal residence time and sustained drug release along with higher in vitro efficacy, safety and patient compliance.